Comment on "Hydrogen Balmer beta: The separation between line peaks for plasma electron density diagnostics and self-absorption test". (July 2015) - Gautam, Ghaneshwar; Surmick, David M.; Parigger, Christian G.
Abstract: In this letter, we present a brief comment regarding the recently published paper by Ivković et al., J Quant Spectrosc Radiat Transf 2015;154:1–8. Reference is made to previous experimental results to indicate that self absorption must have occurred; however, when carefully considering error propagation, both widths and peak-separation predict electron densities within the error margins. Yet the diagnosis method and the presented details on the use of the hydrogen beta peak separation are viewed as a welcomed contribution in studies of laser-induced plasma. Abstract : Highlights: Balmer series H β line for determination of electron density. Compare FWHM with peak-separation method. Apply to laser induced plasma characterization. Comment on self-absorption.